Ascorbic acid loaded PLGA nanoparticles gel as potential oral squamous cell carcinoma site-specific treatment - Nurul Ain Mohammad Hamdi (Kulliyyah of Pharmacy, International islamic University Malaysia, 2021)
Oral squamous cell carcinoma (OSCC) represents the majority of oral cancer. Chemotherapy is commonly used to treat OSCC especially as the disease advanced. However, conventional chemotherapy is associated with terrible adverse effects and the occurrence of chemoresistance which causes treatment failure. Therefore, the quest for a more effective and safer alternative has intensified. High dose ascorbic acid has been evidenced to confer anticancer effects via generation of reactive oxygen species (ROS) and through epigenetic mechanisms. Poly lactic-co-glycolic acid (PLGA) was used as the encapsulating polymer for the delivery of ascorbic acid to the cancer cells. A rapid UV-visible spectrophotometric method was validated as per ICH guideline and applied throughout this study for the quantification of ascorbic acid. Double emulsion solvent evaporation method was used to fabricate ascorbic acid loaded PLGA (AA-PLGA) nanoparticles. Optimisation of formulation was carried out by multilevel categoric full factorial design based on different surfactant concentrations and surfactant types used in the primary emulsion. The particle size of the optimised formulation was found to be 252 ± 2.98 nm, polydispersity index (PDI) of 0.151 ± 0.02, zeta potential of -20.93 ± 0.87 mV and encapsulation efficiency of 69.73 ± 1.07%. Scanning electron microscope images revealed the spherical shape of nanoparticles. The drug release behaviour exhibited a biphasic pattern namely initial burst release followed by slower release. The optimised nanoparticles formulation was further incorporated into different concentrations of Carbopol® gel. The pH of the prepared formulations was well within the pH range of the oral cavity which is between 6.2 – 7.6. Statistical analysis indicated that Carbopol® concentration significantly (p-value < 0.05) affected viscosity, spreadability and mucoadhesion of the gels. The properties of the prepared formulations were compared with a Carbopol® based commercial product (Kin Care) as a reference. Carbopol® polymer with a strength of 1% was chosen as the optimum gelling agent for AA-PLGA nanoparticles gel. The viscosity of the formulation with 1% Carbopol® was slightly higher (p-value < 0.05) than the commercial product, yet the spreadability and adhesion results were comparable (p-value > 0.05). The rheological study showed that all the gels exhibited a pseudoplastic behaviour which is desirable as it facilitates the flow of gel out of the tube and can form a viscous gel at the application site. Besides, the optimum gel formulation exhibited a zero-order kinetic release of ascorbic acid nanoparticles for 6 hours duration. Hence, it is a good candidate for topical application on the oral mucosa. The optimised AA-PLGA nanoparticles were subjected to cytotoxic assay against the OSCC SCC-25 cell line. Through in vitro cytotoxicity study, AA-PLGA nanoparticles mediated a significant (p-value < 0.05) reduction of cancer cell viability in a dose-dependent manner with an IC50 value of 2420 µg/mL. Severe cellular morphological changes were examined with an inverted microscope after 24 hours of incubation with AA-PLGA nanoparticles evidenced the cancer cell death in the SCC-25 cell line. The results of the present study support the feasibility of AA-PLGA nanoparticles gel to treat OSCC and hope the formulation can open a new avenue for OSCC therapy.